Identification of the CDPK gene family in patchouli and functional analysis in response to continuous cropping stress - Liu, Xiaofeng; Zeeshan Ul Haq, Muhammad; Yu, Jing; Liu, Ya; Yang, Huageng; Cui, Hongguang; Yang, Dongmei; Wu, Yougen (Frontiers in Plant Science, 2023)
To further reveal the molecular mechanisms underlying the formation of continuous cropping disorders in patchouli, this study analyzed the function of calcium dependent protein kinase (CDPK) genes at the molecular level in patchouli continuous cropping disorders. The findings unveiled the presence of 45 PcCDPK genes within the complete patchouli genome dataset. These genes exhibited a range of molecular weights from 50.78 to 78.96 kDa and aliphatic index values spanning from 74.42 to 88.49, and are shown to be hydrophilic proteins. The evolution of 45 PcCDPK members was divided into 4 subfamilies, with a total of 65 pairs of collinear genes. Each PcCDPK contains a STKc-CAMK domain and four EF-hand structures exhibiting a certain degree of conservatism during evolution. Transcriptome data further supported the significance of PcCDPK25 and PcCDPK38 genes, showing substantial upregulation, which was corroborated by qRT-PCR results. The 1629 bp and 1716 bp CDS sequences were obtained by cloning the PcCDPK25 and PcCDPK38 genes, respectively, and subcellular localization showed that both proteins were localized on the plasma membrane. This comprehensive study provides molecular-level confirmation of the pivotal roles played by CDPK genes in the emergence of continuous cropping challenges in patchouli plants, establishing a crucial foundation for a deeper comprehension of the molecular mechanisms underpinning these obstacles. 1 Gene name Gene ID No. of aa MW (kDa) pI II AI GRAVY Subcellular localization PcCDPK1 Pat_A04G087900.m1 545 62.